2021
DOI: 10.5144/0256-4947.2021.369
|View full text |Cite
|
Sign up to set email alerts
|

Post-thyroidectomy complications in southwestern Saudi Arabia: a retrospective study of a 6-year period

Abstract: BACKGROUND: Thyroidectomy is the surgical removal of all or part of the thyroid gland for non-neoplastic and neoplastic thyroid diseases. Major postoperative complications of thyroidectomy, including recurrent laryngeal nerve injury, hypocalcemia, and hypothyroidism, are not infrequent. OBJECTIVE: Summarize the frequency of surgical complications of thyroidectomy. DESIGN: Retrospective. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
1
11
2
Order By: Relevance
“…Compared with other conservative procedures, total thyroidectomy has been reported to have a higher risk of nerve injury. 6,16 However, our data showed no significant relationship between the extent of thyroidectomy and the risk of RLN injury. Karamanakos et al 1 also found no relationship between the extent of thyroidectomy and the risk of RLN injury in their univariate analysis only.…”
Section: (contrasting
confidence: 69%
“…Compared with other conservative procedures, total thyroidectomy has been reported to have a higher risk of nerve injury. 6,16 However, our data showed no significant relationship between the extent of thyroidectomy and the risk of RLN injury. Karamanakos et al 1 also found no relationship between the extent of thyroidectomy and the risk of RLN injury in their univariate analysis only.…”
Section: (contrasting
confidence: 69%
“…Process and behavioral outcomes are just one way to measure impact. Results related to postoperative quality of life and patient satisfaction should be considered [25][26][27][28][29]. Similarly, the feedback and opinions of medical staff are equally important.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows the incidence of post-thyroidectomy hematomas in different cities in Saudi Arabia [9][10][11][12][13]. Although hematoma is frequently seen within the first six hours after surgery, bleeding can still occur up to 24 hours after surgery [6].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of hematoma formation in our cohort was 0.8%, which is in line with previous studies [ 1 , 4 , 5 , 8 ]. Table 3 shows the incidence of post-thyroidectomy hematomas in different cities in Saudi Arabia [ 9 - 13 ].…”
Section: Discussionmentioning
confidence: 99%